A risk score based on baseline risk factors for predicting mortality in COVID-19 patients. (3rd June 2021) - Chen, Ze; Chen, Jing; Zhou, Jianghua; Lei, Fang; Zhou, Feng; Qin, Juan-Juan; Zhang, Xiao-Jing; Zhu, Lihua; Liu, Ye-Mao; Wang, Haitao; Chen, Ming-Ming; Zhao, Yan-Ci; et al.
Abstract: Background: To develop a sensitive and clinically applicable risk assessment tool identifying coronavirus disease 2019 (COVID-19) patients with a high risk of mortality at hospital admission. This model would assist frontline clinicians in optimizing medical treatment with limited resources. Methods: 6415 patients from seven hospitals in Wuhan city were assigned to the training and testing cohorts. A total of 6351 patients from another three hospitals in Wuhan, 2169 patients from outside of Wuhan, and 553 patients from Milan, Italy were assigned to three independent validation cohorts. A total of 64 candidate clinical variables at hospital admission were analyzed by random forest and least absolute shrinkage and selection operator (LASSO) analyses. Results: Eight factors, namely, O xygen saturation, blood U rea nitrogen, R espiratory rate, admission before the date the national M aximum number of daily new cases was reached, A ge, P rocalcitonin, C -reactive protein (CRP), and absolute N eutrophil counts, were identified as having significant associations with mortality in COVID-19 patients. A composite score based on these eight risk factors, termed the OURMAPCN-score, predicted the risk of mortality among the COVID-19 patients, with a C-statistic of 0.92 (95% confidence interval [CI] 0.90–0.93). The hazard ratio for all-cause mortality between patients with OURMAPCN-score >11 compared with those with scores ≤ 11 was 18.18 (95% CI 13.93–23.71; p < .0001). The predictive performance, specificity, and sensitivity of the score were validated in three independent cohorts. Conclusions: The OURMAPCN score is a risk assessment tool to determine the mortality rate in COVID-19 patients based on a limited number of baseline parameters. This tool can assist physicians in optimizing the clinical management of COVID-19 patients with limited hospital resources.